Elucidating the Key Role of the Fungal Mycelium on the Biodegradation of N-Pentane as a Model Hydrophobic Voc - Diaz-Robles, L (Elsevier Ltd, 2016)
The role of the aerial mycelium of the fungus Fusarium solani in the biodegradation of n-pentane was evaluated in a continuous fungal bioreactor (FB) to determine the contribution of the aerial (hyphae) and non-aerial (monolayer) fungal biomass. The experimental results showed that although the aerial biomass fraction represented only 25.9(±3)% on a dry weight basis, it was responsible for 71.6(±4)% of n-pentane removal. The FB attained a maximum elimination capacity (ECmax) of 680(±30) g m-3 h-1 in the presence of fungal hyphae (which supported an interfacial area of 5.5(±1.5) × 106 m2 m-3). In addition, a mathematical model capable of describing n-pentane biodegradation by the filamentous fungus was also developed and validated against the experimental data. This model successfully predicted the influence of the aerial biomass fraction and its partition coefficient on the n-pentane removal, with EC decreasing from 680(±30) g m-3 h-1 to values of 200(±14) g m-3 h-1 when the dimensionless partition coefficient increased from 0.21(±0.09) with aerial biomass to 0.88(±0.06) without aerial biomass. © 2016 Elsevier Ltd.